2000
DOI: 10.1093/molehr/6.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sex chromosome aneuploidy in sperm nuclei from 47,XXY and 46,XY/47,XXY males: comparison with fertile and infertile males with normal karyotype

Abstract: Sex chromosome aneuploidy was assessed in spermatozoa from a 47,XXY male and a 46,XY/47,XXY male using three colour fluorescence in-situ hybridization (FISH) and compared with two control groups. The first group included subjects of proven fertility and the second infertile males with normal constitutional karyotype. The frequencies of XX and YY disomic, XY hyperhaploid and diploid spermatozoa were significantly increased in the 47,XXY male compared to subjects from the two control groups (P < 0.0001). For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 35 publications
5
54
0
5
Order By: Relevance
“…Klinefelter's syndrome accounted for 5.04 % of all infertile males, and 97.45 % of Klinefelter patients had AS, as did four out of six cases with karyotypes 46,XY/47,XXY. These findings are in accordance with previous reports where focal spermatogenesis failure and severe OS were found in cases with 46,XY(X)/47,XXY mosaic karyotypes [15]. The current study further supports the theory that a superabundance of X chromosomes could affect the male-determining function by inhibiting maturity, hence promoting degenerative changes in the testis convoluted tubule and thus affecting spermatogenesis, ultimately resulting in varying degrees of related androgen dysfunctions [13].…”
Section: Discussionsupporting
confidence: 93%
“…Klinefelter's syndrome accounted for 5.04 % of all infertile males, and 97.45 % of Klinefelter patients had AS, as did four out of six cases with karyotypes 46,XY/47,XXY. These findings are in accordance with previous reports where focal spermatogenesis failure and severe OS were found in cases with 46,XY(X)/47,XXY mosaic karyotypes [15]. The current study further supports the theory that a superabundance of X chromosomes could affect the male-determining function by inhibiting maturity, hence promoting degenerative changes in the testis convoluted tubule and thus affecting spermatogenesis, ultimately resulting in varying degrees of related androgen dysfunctions [13].…”
Section: Discussionsupporting
confidence: 93%
“…CCSS enables a maximal sampling of the whole extracted tissue while screening dozens of testicular cell, including post-meiotic cells, with a high level of confidence [25,26] and a screening of more than 1,000 spermatogonia and 900 primary spermatocytes for each of the 11 biopsy samples. As expected, based on lymphocyte karyotypes in non-mosaic KS men, and similar to Rives et al [11] and Yamamoto et al [23], who identified between 88.5 and 100 % 47,XXY spermatogonia in testicular biopsies, we found around 90 % spermatogonia with 47,XXY and 10 % with 46,XY, independently of whether or not patients produced testicular sperm. It needs to be specified that Yamamoto et al [23] did not observe any testicular XY cells in negative cases.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is widely reported that men with KS have higher rates of sex and autosomal aneuploidy [5][6][7][8][9][10][11]. Two approaches on the ability of 47,XXY testes to yield postmeiotic cells exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, there is an increased likelihood of having a child with a chromosomal imbalance involving the X chromosome. [17][18][19] New developments in assisted reproductive technologies, such as testicular sperm extraction and intracytoplasmic sperm injection, may offer men with nonmosaic KS and their partners the possibility of conception. 20 However, healthy deliveries after these procedures are rare, and concern regarding the possibility of transmitting chromosomal abnormalities exists.…”
Section: Genetic Implicationsmentioning
confidence: 99%